Peningkatan Produktivitas UMKM ‘Kopi Thung’ melalui Sinergi Media Sosial dan Media Konvensional - Saudah, Saudah; Maulana, Muhammad Naufal; Ismawati, Aini Laila; Aprianto, Rafly (Journal of Indonesian Society Empowerment, 2025)
The main challenge for Micro, Small, and Medium Enterprises (MSMEs) is the limited access to knowledge and technology that can support the growth of their businesses. For MSMEs to succeed, they must choose between remaining in the same place or advancing through innovation. This challenge is also faced by the owner of Kopi Thung, an MSME located in Sidoasri Village, Sumbermanjing Wetan, Malang Regency, East Java, Indonesia. The lack of support in these areas led the business to operate in a simple and suboptimal manner. This training, involving six innovative methods, has had a significant positive impact on the small industry, providing new breakthroughs for marketing products. The aim of this training is to create a more advanced impact, helping the business become better known to the outside world and utilizing social media as a modern breakthrough tool, alongside improving the efficiency and appeal of conventional media. The methods used in this training include initial discussions, logo design, packaging design, product photography practice, social media caption writing practice, and social media management training focused on Instagram. As a result of this training, the business owner has become more open to and knowledgeable about marketing products through social media, and the innovations in logo and packaging have become fresher and more up-to-date. Tantangan terbesar bagi pelaku Usaha Mikro, Kecil, dan Menengah (UMKM) adalah terbatasnya akses terhadap pengetahuan dan teknologi yang dapat mendukung pertumbuhan bisnis mereka. Untuk mencapai kesuksesan, UMKM dihadapkan pada pilihan untuk tetap beroperasi dengan cara konvensional atau beradaptasi dengan inovasi baru yang dapat mendorong kemajuan. UMKM Kopi Thung di Desa Sidoasri, Sumbermanjing Wetan, Kabupaten Malang, Indonesia, menjadi contoh nyata bagaimana kurangnya dukungan teknologi menghambat potensi maksimal dari usaha ini. Melalui pelatihan yang melibatkan enam metode inovatif—termasuk desain logo, kemasan produk, fotografi produk, pembuatan caption untuk media sosial, serta pengelolaan media sosial dengan fokus pada Instagram—pelatihan ini berhasil memberikan dampak positif. Hasilnya, pemilik usaha menjadi lebih terbuka terhadap pemasaran digital dan inovasi dalam logo serta kemasan produk, yang membuatnya lebih menarik dan segar. Keberhasilan ini tidak hanya menunjukkan dampak lokal, tetapi juga menggambarkan bagaimana adopsi teknologi digital dapat meningkatkan daya saing UMKM secara global, membuka peluang lebih besar dalam pasar internasional, dan memberi kontribusi pada pengembangan ekonomi yang berkelanjutan.